Pengaruh urine sapi dan ekstrak tauge terhadap keberhasilan tumbuh setek batang melati (Jasminum sambac L.) - Mulyaningsih, Yanyan; Tobing, Oktavianus Lumban; Sihombing, Zuena Silvani (JURNAL AGRONIDA, 2025)
Jasmine are generally propagated through stem cuttings. However, this method encounters several challenges, particularly the low ability of cuttings to develop roots. The success and growth of jasmine stem cuttings can be enhanced by applying natural plant growth regulators, such as cow urine and mung bean sprout extract. This study aimed to evaluate the effects of cow urine and mung bean sprout extract on the success rate and growth performance of jasmine stem cuttings. The experiment was conducted using a factorial completely randomized design (CRD) with three replications. The first factor was the concentration of cow urine at four levels: 0 mL/L, 10 mL/L, 20 mL/L, and 30 mL/L. The second factor was the concentration of mung bean sprout extract at four levels: 0%, 20%, 40%, and 60%. The results indicated that the application of cow urine at a concentration of 30 mL/L produced higher shoot length (5–8 WAP), number of shoots (7–8 WAP), and root length of jasmine stem cuttings compared to those without cow urine treatment. Moreover, the application of 40% mung bean sprout extract in combination with 30 mL/L cow urine resulted in significantly higher percentages of sprouted cuttings, surviving cuttings, and rooted cuttings compared to combinations with other cow urine treatments.